The Adsorption of Pb, Zn, Cu, Ni, and Cd by Modified Ligand in a Single Component Aqueous Solution: Equilibrium, Kinetic, Thermodynamic, and Desorption Studies. (18th May 2017) - Igberase, E.; Osifo, P.; Ofomaja, A.
Abstract : In this investigation, an amino functionalized adsorbent was developed by grafting 4-aminobenzoic acid onto the backbone of cross-linked chitosan beads. The 3 sets of beads including chitosan (CX), glutaraldehyde cross-linked chitosan (CCX), and 4-aminobenzoic acid grafted cross-linked chitosan (FGCX) were characterized by FTIR, XRD, SEM, and TGA. The water content and amine concentration of FGCX were determined. The effect of adsorption parameters was studied and the optimum was used for further studies. Equilibrium data was obtained from the adsorption experiment carried out at different initial concentration; the data were applied in isotherm, thermodynamics, and kinetic studies. The Langmuir and Dubinin-Kaganer-Radushkevich (DKR) models were successful in describing the isotherm data for the considered metal ions while the Freundlich and Temkin model fit some of the considered metal ions. Pseudo-second-order and intraparticle model described the kinetic data quite well. Thermodynamic parameters such as Gibb's free energy change (Δ G o ), enthalpy change (Δ H o ), and entropy change (Δ S o ) were calculated and the results showed that the adsorption of Pb, Cu, Ni, Zn, and Cd ions onto FGCX is spontaneous and endothermic in nature. Regeneration of the spent adsorbent was efficient for the considered metal ions.